ANALISIS DAYA SAING INDUSTRI MANUFAKTUR JAWA TIMUR: SEBUAH PENDEKATAN SPASIAL - Handoyo, Rossanto Dwi (Jurnal Organisasi dan Manajemen, 2016)
This research aims to identify the pre-eminent product based on comparative advantages and Location Quotion concept as well as spatial aspect. The analysis result confirm that spatial concentration of manufacture sector industry in East Java located in six region which is Kota Surabaya, Kota Kediri, Kabupaten Sidoarjo, Kabupaten Gresik, Kota Malang, and Kabupaten Pasuruan. This six region dominate manufacture industrial output in East Java about 85%. It means that the changing of supply and demand side in these regions will influence to the manufacture industrial performance in east Java as a whole. Manufacture industry in East Java is still dominated by food, beverages and tobacco industries (ISIC 31); textiles, shirt and skin (ISIC 32); wood based industry (ISIC 3.6), paper and print industry (ISIC 3.4) and transportation industry (ISIC 3.8). The analysis result using RTA index shows that East Java Province has export comparative advantages in lead and article thereof (HS 78), explosive; matches; pyrotechinic product (HS 36), cereals (HS 10), zinc and particles thereof (HS 79), tools, implements, cutlery, spoons (HS 82), dan dairy product (HS 04). The analysis on spatial association of output of East Java manufacture industry result several findings. The research results that there is positive spatial autocorrelation, in which high value region is surrounded by the high value regions, otherwise the low value region is surrounded by the low value regions. Spatial lag model also shows the importance of manufacturing industry output growth rate of neighboring regions. Spatial lag models show that the growth of the industrial output in the neighbour region plays an important role as determinant factor of industrial output in one region in the East Java Province. Perubahan struktural pada perekonomian modern ditunjukkan oleh semakin besarnya peran sektor industri manufaktur dalam suatu perekonomian. Kebijakan yang berorientasi spasial dan regional merupakan  salah satu faktor kunci yang dapat mendukung pemerintah pusat dan daerah dalam merumuskan dan mengimplementasikan kebijakan pembangunan di sektor industri. Penelitian ini bertujuan untuk melakukan pemetaan daya saing berdasarkan berdasarkan aspek kewilayahan (spasial) di Provinsi Jawa Timur. Industri manufaktur dari aspek kewilayahan terkonsentrasi pada enam wilayah yaitu Surabaya, Kota Kediri, Sidoarjo, Gresik, Kota Malang, dan Pasuruan. Ke enam wilayah ini mendominasi output  industri manufaktur di Jawa Timur hingga 85%. Hasil analisis daya saing menggunakan indek RTA (revealed comparative trade advantage) menunjukkan bahwa Jawa Timur secara keseluruhan memiliki keunggulan komparatif dalam ekspor untuk komoditi seperti timbal dan produk turunannya (HS 78), pyrotechinic dan produk turunannya (HS 36), cereals (HS 10), seng dan produk turunannya (HS 79), perkakas dan produk sejenis (HS 82), dan produk terbuat dari susu (HS 04). Analisis keterkaitan spasial industri manufaktur dengan cluster di Jawa Timur menunjukkan ada keterkaitan spasial yang positif (positive spatial autocorrelation), dimana daerah yang memiliki daya saing yang tinggi dikelilingi oleh daerah yang nilainya tinggi pula. Analisis menggunakan Model spatial lag juga menunjukkan faktor-faktor penentu daya saing industri manufaktur (berdasarkan teori berlian/Diamond Theory dari Porter) daerah tetangga sangat penting sebagai penentu daya saing industri  manufaktur di masing-masing Kabupaten/Kota di Jawa Timur.